Accounting for a planned migration through ethnic identity talk. (June 2015) - Jurva, Katrina; Jasinskaja-Lahti, Inga
Previous discursive research on ethnic identity has suggested the complex and multi-faceted nature of accomplishing membership in an ethnic group. In this paper, we explore how ethnic identity claims may be used as a resource in accounting for behavior seen as open to the group, namely a planned migration to one's ancestral homeland. A discursive psychological approach is used to analyze focus group data with potential ethnic return migrants, specifically, adults with Finnish roots who intend to migrate to Finland. Ethnic identity was accomplished in subtle ways by drawing on one's roots and a familiarity with Finnish culture, as well as by accomplishing a preference for Finland. Working up Finnish ethnic identity in these ways allowed participants to account for the planned migration, which was typically constructed as a natural, inevitable and/or long- and highly-desired action. The findings highlight the importance of considering the social action of ethnic identity talk, particularly in light of previous studies that have found ethnic return migrants' pre-migration ethnic identities to be pronounced.